FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.